Spatial correlation of dengue cases based on climate changes in Selangor for year 2013 to 2015 / Rabiatul Adawiyah Ab Halim - Ab Halim, Rabiatul Adawiyah (2018)
Dengue fever is an infectious mosquito borne disease that places a heavy burden on global disease and also on public health systems in Malaysia as well as on most of the tropical countries around the world. Little is known the climate changing association of dengue disease. The aim of this study is to analyse the spatial correlation of dengue cases from year 2013 to 2015 based on climatic changing condition in Selangor using Geographic Information System (GIS). The correlation of dengue cases based on the calculation of temperature value in Selangor and it is then mapped based on monthly number of dengue cases for three years. Kernel Density estimation was used for hotspot analysis on dengue cases. Then, Landsat 8 OLI were used to extract the value of temperature to be correlated with dengue cases. Correlation in 2013 and 2014 are given with R² value is 10% decreasing from July to December. It shows that, temperature is less significantly contributing to dengue cases due to the inconsistently temperature during July to December. On the other hand, correlation between 2014 and 2015 from January to April are given with R² value is 15% increasing. Therefore, temperature is more significantly contributing to dengue cases during January to April. This is because, that most of cases were concentrated in the first half of the year, mainly in March and April, underlining the known seasonality of dengue fever. Then, the mean annual temperature for the period were 24°C and 29°C for monthly maximum temperature. The range of temperature around 24°C to 33°C is very conducive for mosquito breeding cycle as an increase number of times, that mosquito breeds will also increase the likelihood of emergence of dengue outbreak. In the conclusion, dengue cases positively correlated with climate changes in Selangor for year 2013 to 2015.